Conserved grassland forage – is the composition of cow's milk influenced by feeding silage compared to hay? - Sabrina P. Van den Oever; Katrin Bauer; Andreas Haselmann; Matthias Schreiner; Birgit Fuerst-Waltl; Werner Zollitsch; Qendrim Zebeli; Helmut K. Mayer; Wilhelm Knaus (International Dairy Journal, 2026)

Correction to: Approach for the vertical wind speed profile implemented in the UTCI basics blocks UTCI applications at the urban pedestrian level - Hyunjung Lee; Sookuk Park; Helmut Mayer (International Journal of Biometeorology, 2025)

Approach for the vertical wind speed profile implemented in the UTCI basics blocks UTCI applications at the urban pedestrian level - Hyunjung Lee; Sookuk Park; Helmut Mayer (International Journal of Biometeorology, 2025)
The applicability of the Universal Thermal Climate Index (UTCI) at the urban pedestrian level is analysed in relation to the approach for the vertical wind speed profile (VWSP) used in the UTCI basics. As the UTCI refers to the human-biometeorological reference height ( z h−b ) of 1.1 m above ground level (agl), all meteorological input variables for UTCI calculations should also be originated from z h−b . Since the development of the UTCI considered meteorological conventions for stations routinely operated by national weather services, the wind speed ( v ) as one of four meteorological input variables is initially required at 10 m agl ( v 10 m ). In order to calculate v at z h−b from v 10 m , the logarithmic law for the VWSP is implemented in the UTCI basics, but only for neutral atmospheric stability and a roughness length ( z 0 ) for short-cut grassland ( z 0 = 0.01 m). This methodological approach cannot be changed in the UTCI basics so far. The UTCI developers also recommend the application of the same logarithmic law, if v values at lower heights have to be extrapolated to 10 m agl. However, the use of this VWSP approach disregards basic air flow findings and principles in the urban canopy layer (UCL). If the UTCI is nevertheless applied at the urban pedestrian level, inaccuracies in the UTCI values will occur. With reference to z 0 = 0.80 m, which is more typical for the UCL, they can be up to 7 K, as shown in the example of three different climate zones.

“Exotic” seeds from Southern Africa as potential Novel Foods? – Chemical composition of manketti nuts (Schinziophyton rautanenii) and ushivi beans (Guibourtia coleosperma) - Sabrina P. Van den Oever; Cecilia K. Maruta; Matthias Schreiner; Helmut K. Mayer (Food Research International, 2024)

Evaluation of spectral handheld devices for freshness assessment of carp and trout fillets in relation to standard methods including non-targeted metabolomics - Bernadette Moser; Zora Jandric; Christina Troyer; Lukas Priemetzhofer; Konrad J. Domig; Henry Jäger; Sabrina P. van den Oever; Helmut K. Mayer; Stephan Hann; Andreas Zitek (Food Control, 2023)

„Rohstoffpark Enns“ - Kurt Bernegger; Christian Mlinar; Helmut Lugmayr; Gerhard Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2023)
Zusammenfassung Der „Rohstoffpark Enns“ ist ein Industriestandort der Fa. Bernegger aus Molln. Im Endzustand umfasst dieser neben allgemeiner Infrastruktur (Bahnanschluss, zentrale Abwasserbehandlung etc.) auf 20 ha sieben Abfallbehandlungsanlagen. Der Zweck dieser Anlagen besteht in der Maximierung rückgewinnbarer Wertstoffe (Metalle, Kunststoffe, mineralische Rohstoffe) als Ersatz für Primärmaterial, der Erzeugung von grüner Energie (Wärme für 7000 und Strom für 15.000 Haushalte) und der Minimierung von zu deponierenden Rückständen. Folgende zentrale Anlagen des Rohstoffpark Enns sind aktuell in Umsetzung: ● eine Kunststoffsortieranlage (Kooperation ARA, Grüner Punkt und Bernegger) in welcher 100.000 t/a Leichtverpackungen („Gelber-Sack-Materialien“) mittels 38 Nahinfrarot-Sortiergeräten zur wertstofflichen Verwertung aufbereitet werden. ● eine seit 2006 bestehende Shredder-Rückstands-Aufbereitungsanlage (SRA) zur Gewinnung von Kunststoffen und Metallen aus Rückständen v. a. aus der Schrottaufbereitung. Dies erfolgt mittels Zerkleinerung, Klassierung und einer Vielzahl von unterschiedlichen Sortierungsschritten. ● eine 2024 in Betrieb gehende Thermische Metallgewinnung zur Rückgewinnung von Metallen v. a. aus den feinkörnigen, gering metallhaltigen und sehr stark verwachsenen Rückständen der SRA. Bei diesem Herstellungsprozess kommt ein von der Fa. Bernegger – gemeinsam mit der Fa. Küttner und mit Unterstützung von der Montanuniversität Leoben und der RWTH Aachen – über mehrere Jahre entwickeltes pyrometallurgisches Verfahren zum Einsatz. Damit wird neben Schwarzkupfer auch ein mineralisches Bindemittel und zinkhältiger Staub erzeugt sowie gleichzeitig durch den autothermen Prozess, Strom und Dampf produziert.

Air pollution assessment in Seoul, South Korea, using an updated daily air quality index - Hyunjung Lee; Jinhyo Lee; Seokryul Oh; Sookuk Park; Helmut Mayer (Atmospheric Pollution Research, 2023)

Geospatial Information Research: State of the Art, Case Studies and Future Perspectives - Ralf Bill; Jörg Blankenbach; Martin Breunig; Jan-Henrik Haunert; Christian Heipke; Stefan Herle; Hans-Gerd Maas; Helmut Mayer; Liqui Meng; Franz Rottensteiner; Jochen Schiewe; Monika Sester; et al. (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2022)
Geospatial information science (GI science) is concerned with the development and application of geodetic and information science methods for modeling, acquiring, sharing, managing, exploring, analyzing, synthesizing, visualizing, and evaluating data on spatio-temporal phenomena related to the Earth. As an interdisciplinary scientific discipline, it focuses on developing and adapting information technologies to understand processes on the Earth and human-place interactions, to detect and predict trends and patterns in the observed data, and to support decision making. The authors – members of DGK, the Geoinformatics division, as part of the Committee on Geodesy of the Bavarian Academy of Sciences and Humanities, representing geodetic research and university teaching in Germany – have prepared this paper as a means to point out future research questions and directions in geospatial information science. For the different facets of geospatial information science, the state of art is presented and underlined with mostly own case studies. The paper thus illustrates which contributions the German GI community makes and which research perspectives arise in geospatial information science. The paper further demonstrates that GI science, with its expertise in data acquisition and interpretation, information modeling and management, integration, decision support, visualization, and dissemination, can help solve many of the grand challenges facing society today and in the future.

Pulvermetallurgische Herstellung von innovativen Hochtemperaturwerkstoffen - Helmut Clemens; Svea Mayer; Martin Heilmaier (BHM Berg- und Hüttenmännische Monatshefte, 2021)
Zusammenfassung Die pulvermetallurgische Herstellung von Bauteilen aus innovativen Werkstoffen, wie intermetallischen Titanaluminiden und Refraktärmetallsiliziden, bietet eine Vielfalt von Anwendungsmöglichkeiten in modernen Flugzeugtriebwerken und Verbrennungsmotoren. Für die Produktion von hochwertigen Legierungspulvern und deren Verarbeitung stehen mehrere industriell relevante Verfahren bereit.

A socio‐ecological model for predicting impacts of land‐use and climate change on regional plant diversity in the Austrian Alps - Iwona Dullinger; Andreas Gattringer; Johannes Wessely; Dietmar Moser; Christoph Plutzar; Wolfgang Willner; Claudine Egger; Veronika Gaube; Helmut Haberl; Andreas Mayer; Andreas Bohner; Christian Gilli; et al. (Global Change Biology, 2020)
Climate and land‐use change jointly affect the future of biodiversity. Yet, biodiversity scenarios have so far concentrated on climatic effects because forecasts of land use are rarely available at appropriate spatial and thematic scales. Agent‐based models (ABMs) represent a potentially powerful but little explored tool for establishing thematically and spatially fine‐grained land‐use scenarios. Here, we use an ABM parameterized for 1,329 agents, mostly farmers, in a Central European model region, and simulate the changes to land‐use patterns resulting from their response to three scenarios of changing socio‐economic conditions and three scenarios of climate change until the mid of the century. Subsequently, we use species distribution models to, first, analyse relationships between the realized niches of 832 plant species and climatic gradients or land‐use types, respectively, and, second, to project consequent changes in potential regional ranges of these species as triggered by changes in both the altered land‐use patterns and the changing climate. We find that both drivers determine the realized niches of the studied plants, with land use having a stronger effect than any single climatic variable in the model. Nevertheless, the plants' future distributions appear much more responsive to climate than to land‐use changes because alternative future socio‐economic backgrounds have only modest impact on land‐use decisions in the model region. However, relative effects of climate and land‐use changes on biodiversity may differ drastically in other regions, especially where landscapes are still dominated by natural or semi‐natural habitat. We conclude that agent‐based modelling of land use is able to provide scenarios at scales relevant to individual species distribution and suggest that coupling ABMs with models of species' range change should be intensified to provide more realistic biodiversity forecasts.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Kornfeinung ausscheidungsverfestigter Hochtemperaturferrite mittels Ce-haltiger Einschlüsse - Flora Godor; Alexander Mayerhofer; Peter Presoly; Helmut Clemens; Svea Mayer; Christian Bernhard (BHM Berg- und Hüttenmännische Monatshefte, 2019)

15. Internationale Metallographie-Tagung - Helmut Clemens; Svea Mayer; Michael Panzenböck (BHM Berg- und Hüttenmännische Monatshefte, 2019)

Mikrostrukturelle Charakterisierung einer pulvermetallurgisch hergestellten mehrphasigen TiAl-Legierung - Michael Burtscher; Fabian Pürstl; Martin Schloffer; Svea Mayer; Helmut Clemens (BHM Berg- und Hüttenmännische Monatshefte, 2019)

To what extent does the air flow initialisation of the ENVI-met model affect human heat stress simulated in a common street canyon? - Hyunjung Lee; Helmut Mayer; Wilhelm Kuttler (International Journal of Biometeorology, 2019)

Thermal comfort of pedestrians in an urban street canyon is affected by increasing albedo of building walls - Hyunjung Lee; Helmut Mayer (International Journal of Biometeorology, 2018)

Wide-Baseline Image Matching with Projective View Synthesis and Calibrated Geometric Verification - Lukas Roth; Andreas Kuhn; Helmut Mayer (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2017)

Validation of the mean radiant temperature simulated by the RayMan software in urban environments - Hyunjung Lee; Helmut Mayer (International Journal of Biometeorology, 2016)

Pulvermetallurgie von intermetallischen Titanaluminiden - Helmut Clemens; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2015)

In-situ High-energy X-ray Diffraction on an Intermetallic β-stabilised γ-TiAl Based Alloy - Petra Erdely; Andreas Stark; Helmut Clemens; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2015)

Phase Transformations and Grain Growth in β-stabilized TiAl Alloys - Thomas Klein; Salar Niknafs; Rian Dippenaar; Helmut Clemens; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2014)

Constitutive Analysis of the Flow Curve Behavior of an Intermetallic b-solidifying γ-TiAl-based Alloy and Microstructural Characterization of the Deformed State - Robert Werner; Janny Lindemann; Helmut Clemens; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2014)

Long‐term analysis of heat waves in Ukraine - Olga Shevchenko; Hyunjung Lee; Sergiy Snizhko; Helmut Mayer (International Journal of Climatology, 2014)
In the past few decades, severe heat waves were representative of the weather conditions in various parts of the world. They had distinctly negative impacts on humans, plants, animals and different economic sectors. Particularly in cities, where most humans are living, their well‐being, efficiency and health were affected, which even caused a relatively high mortality rate. This is why a large interest still exists to analyse heat waves in the past by use of statistical methods. As an investigation on heat waves is not available for the territory of Ukraine up to now, a retrospective analysis was conducted. Its main aims were (1) to determine the frequency of heat wave episodes for this country and (2) to analyse their spatiotemporal distribution, duration and intensity. On the basis of 13 selected stations of the meteorological network of the Ukrainian Hydrometeorological Centre, daily values of maximum air temperature ( T a,max ) in the summer months June to August were used to determine heat wave episodes according to the definition recommended by the IPCC . For all stations, complete and reliable T a,max time series were available for the period 1951–2011. With respect to some stations, the T a,max time series already started some years earlier, e.g. in 1936 for five stations and even in 1911 for four stations. However, the T a,max time series of almost all stations had gaps in the summer months before 1951, particularly in the 1940s of the 20th century. As they could not be filled in a satisfying way, this limitation was considered in the data analysis. The results indicate that most of the heat wave episodes occurred at stations located in Eastern Ukraine. In contrast to other decades, the number of heat wave episodes was highest for almost all stations in the decade 2001–2010. The fewest heat wave episodes were determined for the two decades 1961 to 1980. The longest heat wave duration varied between 7 d in Henichesk (southern seashore) and 24 d in Lugansk (Eastern Ukraine). For many stations, the longest heat wave duration occurred in the first two decades of August 2010, i.e. in the period of the extremely severe heat wave in Western Russia. The intensity of heat waves was analysed by use of the cumulative T a,max excess. The results show that heat waves of the longest duration mostly represented the strongest heat waves. The 24‐d heat wave 2010 in Lugansk was the strongest in the investigation period quantified by a cumulative T a,max excess of 128 °C.

Analysis and simulation of dynamic response behavior of Scots pine trees to wind loading - Dirk Schindler; Hannes Fugmann; Helmut Mayer (International Journal of Biometeorology, 2013)

Gefüge und Eigenschaften einer mehrphasigen intermetallischen Titanaluminidlegierung für innovative Leichtbauanwendungen - Andrea Gaitzenauer; Mathias Schenk; Wolfgang Kuchling; Helmut Clemens; Patrick Voigt; Robert Hempel; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2013)

Eigenschaftsoptimiertes Warmumformen einer intermetallischen Titanaluminid-Legierung - Andrea Gaitzenauer; Martin Müller; Helmut Clemens; Patrick Voigt; Robert Hempel; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2012)

Wind effects on trees - Dirk Schindler; Jürgen Bauhus; Helmut Mayer (European Journal of Forest Research, 2012)

Coherent response of a group of plantation-grown Scots pine trees to wind loading - Dirk Schindler; Hannes Fugmann; Jochen Schönborn; Helmut Mayer (European Journal of Forest Research, 2012)

On Phase Equilibria and Phase Transformations in β/γ-TiAl Alloys – A Short Review - Svea Mayer; Christian Sailer; Thomas Schmoelzer; Helmut Clemens; Thomas Lippmann; Peter Staron; Volker Güther; Masao Takeyama (BHM Berg- und Hüttenmännische Monatshefte, 2011)

Intermetallisches Titanaluminid – Ein innovativer Leichtbauwerkstoff für Hochtemperaturanwendungen - Helmut Clemens; Svea Mayer (BHM Berg- und Hüttenmännische Monatshefte, 2011)

Modelling radiation fluxes in simple and complex environments: basics of the RayMan model - Andreas Matzarakis; Frank Rutz; Helmut Mayer (International Journal of Biometeorology, 2010)

Water fluxes within beech stands in complex terrain - Jutta Holst; Rüdiger Grote; Christine Offermann; Juan Pedro Ferrio; Arthur Gessler; Helmut Mayer; Heinz Rennenberg (International Journal of Biometeorology, 2010)

The effects of a regeneration felling on photosynthetic photon flux density and regeneration growth in a Nothofagus pumilio forest - Juan Caldentey; Helmut Mayer; Manuel Ibarra; Alvaro Promis (European Journal of Forest Research, 2009)

The Rapid Retreat of Jakobshavns Isbræ, West Greenland: Field Observations of 2005 and Structural Analysis of its Evolution - Helmut Mayer; Ute C. Herzfeld (Natural Resources Research, 2008)

The effect of forest management on trace gas exchange at the pedosphere–atmosphere interface in beech (Fagus sylvatica L.) forests stocking on calcareous soils - Michael Dannenmann; Rainer Gasche; Astrid Ledebuhr; Thomas Holst; Helmut Mayer; Hans Papen (European Journal of Forest Research, 2007)

Modelling radiation fluxes in simple and complex environments—application of the RayMan model - Andreas Matzarakis; Frank Rutz; Helmut Mayer (International Journal of Biometeorology, 2007)

CO2 fluxes of a Scots pine forest growing in the warm and dry southern upper Rhine plain, SW Germany - Dirk Schindler; Matthias Türk; Helmut Mayer (European Journal of Forest Research, 2006)

Soluble N compound profiles and concentrations in European beech (Fagus sylvatica L.) are influenced by local climate and thinning - Michael Nahm; Thomas Holst; Andreas Matzarakis; Helmut Mayer; Heinz Rennenberg; Arthur Geßler (European Journal of Forest Research, 2006)

Microclimate within beech stands?part II: thermal conditions - Thomas Holst; Helmut Mayer; Dirk Schindler (European Journal of Forest Research, 2004)

Essential trace elements in humans - Daniel R. Mayer; Walter Kosmus; Helmut Pogglitsch; David mayer; Wolfgang Beyer (Biological Trace Element Research, 1993)